Effect of media composition on bioavailability and toxicity of silver and silver nanoparticles in fish intestinal cells (RTgutGC). Issue 10 (25th November 2016) - Minghetti, Matteo; Schirmer, Kristin
Abstract: To understand conditions affecting bioavailability and toxicity of citrate-coated silver nanoparticles (cit-AgNP) and dissolved silver at the luminal enterocyte interface, we exposed rainbow trout ( Oncorhynchus mykiss ) gut cells (RTgutGC) in media of contrasting composition: two amino acid-containing media, one of which was supplemented with proteins, as can be expected during digestion; and two protein and amino acid-free media contrasting low and high chloride content, as can be expected in the lumen of fish adapting to freshwater or seawater, respectively. Dose–response curves were generated measuring cell metabolic activity, membrane and lysosome integrity over a period of 72 hours. Then, nontoxic doses were applied and total silver accumulation, metallothionein and glutathione reductase mRNA levels were determined. The presence of proteins stabilized cit-AgNP keeping them in suspension. Conversely, in protein-free media, cit-AgNP agglomerated and settled, resulting in higher cellular accumulation of silver and toxicity. Chloride concentrations in exposure media modulated the toxicity of AgNO3 but not of cit-AgNP. Moreover, while amino acid-containing media are protective against AgNO3, likely due to the formation of thiolate complexes, they are only partially protective against cit-AgNP. Viability assays indicated that lysosomes are targets of cit-AgNP, supporting the hypothesis that cit-AgNP exert toxicity intracellularly. Metallothionein, a sensor of metal bioavailability, was induced by cit-AgNP in high chloride medium but not in low chloride medium, indicating that chloride might have a role in mobilizing silver from intercellular vesicles. Overall, this study shows that AgNP bioavailability and toxicity in the intestine is linked to its luminal content.